In Situ Nitrogen‐Doping Carbon Aerogel as an Effective Sulfur Host to Immobilize Polysulfides for High Performance Lithium‐Sulfur Battery. Issue 46 (10th December 2020) - Ye, Jinjin; Li, Xueliang; Gao, Wei; Zhu, Yunyun; Cheng, Sheng
Abstract: In‐situ high content N‐doping carbon aerogel (NCA) is successfully prepared via low‐cost m‐phenylenediamine and formaldehyde reaction through the facile sol‐gel method and further high‐temperature carbonization process. NCA material with nanospheres presents the characteristics of large specific surface area and high loading sulfur owing to the specific cross‐linked framework structure. In addition, the NCA/S cathode with high content of nitrogen can achieve strong adsorption to lithium polysulfides (LiPSs) due to its inherent N active sites, and presents outstanding electrochemical performance. In details, the designed NCA/S electrode demonstrates the first discharge capacity of 1247 mAh g −1 at 0.2 C. Moreover, the NCA/S battery also displays excellent electrochemical stability with low capacity attenuation rate of 0.083 % per cycle within 300 cycles at 0.5 C. The remarkable electrochemical properties are mainly ascribed to intense adsorption of evenly‐distributed nitrogen in the carbon material, effectively preventing polysulfide (PS) escaping from host material, restraining shuttle effect and increasing sulfur utilization. Abstract : By inheriting original and in‐situ doping, carbon aerogel with high content of nitrogen (NCA) is successfully prepared through a facile method. NCA material exhibits a specific surface area of 892 m 2  g −1 and a high sulfur loading of 2.4 mg cm −3 as cathode material. NCA/S battery effectively restrains shuttle effect and presents first discharge capacity of 1247 mAh g −1 at 0.2 C. Moreover, it exhibits excellent electrochemical stability with low capacity attenuation rate of 0.083 % per cycle.